O DWÓCH PRÓBACH TRANSCENDENTALNEGO UZASADNIENIA PRAW CZŁOWIEKA - Łącki, Paweł (Wydział Prawa i Administracji UAM, 2006)
Human rights constitute a universal moral paradigm in the contemporary world. Paradoxically, their wide recognition on the practical platform gives rise to numerous doubts as to the possibilities of their theoretical justification. Therefore, the task of justifying human rights is one of the important and still topical questions of the philosophy o f law. Alan Gewirth and Otfried Hòffe try to justify human rights basing their considerations on the conditions that ensure the capability of action and its transcendental nature for the acting subject. Such argumentation seems promising: if one managed to argue convincingly that human rights are necessarily connected with what every man as an object of such actions must necessarily want for him/herself, in other words, with what they rationally want, those rights would then have a strong theoretical foundation. In the critical part of this paper it will be shown why both quoted authors have failed to achieve their intended goal. While Gewirth overestimates the scope of normative rules related to the necessary conditions for actions, Otfried Hoffe introduces moral aspects to those premises, thus making his argumentation of the hermenautics of law character rather than one of their fundamental justification.
ON TWO ATTEMPTS OF TRANSCENDENTAL JUSTIFICATION OF HUMAN RIGHTS